2021
DOI: 10.1016/j.jve.2021.100055
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination with inactivated virus against low pathogenic avian influenza subtype H9N2 does not prevent virus transmission in chickens

Abstract: H9N2 subtype avian influenza has spread dramatically in China ever since first reported in the 1990s. A national vaccination program for poultry was initiated in 1998. Field isolation data show that the widely used inactivated H9N2 vaccine does not provide effective control of the transmission of this low pathogenic avian influenza (LPAI) virus in poultry. Current research has focused on two reasons: (i) insufficient immune response triggered by the vaccination with the inactivated virus, (ii) the occurrence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…Despite significant reductions in H7N9 population size [ 14 ] and positive rates among poultry [ 36 ] since the H7N9 Re-1 vaccine administration, the circulating HP H7N9 AIVs still have a high risk of coinfection with the H9N2 virus in the field. Since the H9N2 virus is basically ubiquitous in Chinese poultry farms, vaccination cannot prevent viral shedding and transmission in chickens after infection [ 37 39 ]. Coinfection may result in the shuffling of individual viral genes and generation of H7N9 reassortants whose phylogenetic topology would closely cluster with H9N2 AIVs and resemble the phylogenetic relationship of the first 5 waves.…”
Section: Resultsmentioning
confidence: 99%
“…Despite significant reductions in H7N9 population size [ 14 ] and positive rates among poultry [ 36 ] since the H7N9 Re-1 vaccine administration, the circulating HP H7N9 AIVs still have a high risk of coinfection with the H9N2 virus in the field. Since the H9N2 virus is basically ubiquitous in Chinese poultry farms, vaccination cannot prevent viral shedding and transmission in chickens after infection [ 37 39 ]. Coinfection may result in the shuffling of individual viral genes and generation of H7N9 reassortants whose phylogenetic topology would closely cluster with H9N2 AIVs and resemble the phylogenetic relationship of the first 5 waves.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the continuous circulation of H9N2 in vaccinated poultry not only hints at an antigenic drift and/or clade replacement by vaccine but also introduces doubt on whether inactivated vaccines are effective at stopping transmission of low pathogenicity avian influenza (LPAI) H9N2 in poultry. Our previous research ( 25 ) indicated the high possibility of transmission in vaccinated chickens with inactivated vaccines. This, consequently, might lead genetic changes toward antigenic mutations.…”
Section: Introductionmentioning
confidence: 99%
“…In the meantime, H9N2 has become the dominant subtype in both chickens and ducks across China, replacing the dominant subtype H5N6 in ducks from 2014 to 2016, which further complicated the epidemiological dynamics [ 9 ]. These evidences revealed that H9N2 are still prevalent in China, serving as an alarm of the potential failure of the H9N2 vaccination [ 52 ], making it imperative to conduct further research on the antigenic characteristics.…”
Section: Discussionmentioning
confidence: 99%